Collision tumour of two nodal metastases (adenocarcinoma and mast cell tumour) in a dog. Issue 3 (22nd September 2020) - Gibson, Danielle; Beck, Samuel; Gonzàlez‐Gasch, Esteban; Harper, Aaron
SUMMARY: An 11‐year‐old female neutered Labrador retriever was referred for a large vulvar mast cell tumour that extended into the vagina. Abdominal ultrasound revealed an enlarged right medial iliac lymph node, and cytology of the node was consistent with an endocrine/neuroendocrine tumour. An approximately 1.5‐cm right anal sac mass was palpated. Medial iliac lymphadenectomy via ventral celiotomy, right anal sacculectomy and marginal vulvar mass resection were performed. Histopathology was consistent with right anal sac adenocarcinoma, vulvar mast cell tumour, and the right medial iliac lymph node showed a metastatic collision of both the adenocarcinoma and mast cell tumour cell populations. Adjunctive chemotherapy and radiotherapy were recommended to address the risk of local recurrence and further metastasis but were declined by the owner. The dog remains alive and asymptomatic with no visible evidence of recurrence 14 months after initial presentation.